2022
DOI: 10.1039/d2cc02476d
|View full text |Cite
|
Sign up to set email alerts
|

Probing the cell delivery of synthetic diubiquitin chains

Abstract: In this study, the live-cell delivery of structurally different synthetic diubiquitin chains was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…123 Thus, lysosomal escape is necessary, which is possible using several pathways, where one idea is to introduce enough positive charge on the surface of COFs via post-synthetic modification. 125…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…123 Thus, lysosomal escape is necessary, which is possible using several pathways, where one idea is to introduce enough positive charge on the surface of COFs via post-synthetic modification. 125…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the cell surface is negatively charged; and thus a positively charged entity may have easier cell penetration, however, the authors suggested that the negative charges on the nanocomposites favoured efficient cell permeability. 123–128 The combined anti-tumour drug delivery of IR783 (achieved by 5 min of 808 nm laser irradiation) was found to be the most effective in terms of cell viability studied by propidium iodide staining. The combination therapy for COF@IR783@CAD with a laser revealed the inhibition of tumour growth in mice.…”
Section: Drug Delivery Using Cofsmentioning
confidence: 99%
See 3 more Smart Citations